Epidemiologia das doenças negligenciadas no Brasil e gastos federais com medicamentos - Leila Posenato Garcia; Luís Carlos G. de Magalh\~aes; Adriana Pacheco Aurea; Carolina Fernandes dos Santos; Raquel Filgueiras de Almeida (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– The World Health Organization (WHO) and Medecins Sans Frontieres recently have proposed the term neglected diseases, referring to those that have a higher occurrence in the developing countries and most neglected, exclusive of developing countries. Leishmaniasis, Chagas disease, trachoma, leprosy, malaria, and various parasites are just some examples of neglected diseases. Given the importance of combating these diseases as a tool on promotion of social and economic development, and in order to support the discussion of the policy on Research and Development (R&D) of medicines in Brazil, this study evaluates the epidemiological situation of neglected diseases with higher prevalence in Brazil. It also analyzes the federal government spending on medicines to treat those diseases, identifying the drugs, dosage forms and their respective costs in the period 2005 to 2008. In this sense, it is observed that despite the high incidence of neglected diseases in Brazil, spending of the Ministry of Health on medicines for the pharmaceutical assistance programs for neglected diseases is scarce if compared to spending on other programs, such as AIDS, for example. It is believed that it reflects the lack of new drugs for the treatment of neglected diseases, that would be, therefore, subject to patent protection, and, consequently, more expensive. On the other hand, Brazil is one of the developing countries that invests more on research of new treatments for neglected diseases. As it has been done on other countries, it could be proposed Public Private Partnerships (PPPs) for R&D on neglected diseases in Brazil, once this country is directly interested in the possible products of such partnerships and has the technical capability to do so.
Keywords: I18; 330